Organocatalytic activation of TMSCN by basic ammonium salts for efficient cyanation of aldehydes and imines - Raj, I. Victor Paul; Suryavanshi, Gurunath; Sudalai, A. (Tetrahedron Letters, 2007)
Basic ammonium salts act as highly effective catalysts for the cyanosilylation of aldehydes and in Strecker-type aminonitrile synthesis using TMSCN as cyanide source at 25 degrees C under extremely mild conditions, affording very good to excellent yields of silylated cyanohydrins and alpha-aminonitriles. (C) 2007 Published by Elsevier Ltd.
Keywords: aldehydes; aminonitriles; cyanohydrin; cyanosilylation; multicomponent reactions; TMSCN

Oxidative Olefination of Benzylamine with an Active Methylene Compound Mediated by Hypervalent Iodine (III) - Rupanawar, Bapurao D.; Veetil, Sruthi M.; Suryavanshi, Gurunath (European Journal of Organic Chemistry, 2019)
Hypervalent iodine-mediated oxidative olefination of amines with an active methylene compound provides a rapid gateway towards the formation of electrophilic alkenes under mild reaction conditions in good to excellent yields. This is an efficient protocol for the preparation of substituted electrophilic alkenes.

Oxidative radical-mediated addition of ethers to quinone imine ketals: an access to hemiaminals - More, Satish G.; Kamble, Rohit B.; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2021)
The highly regioselective synthesis of substituted hemiaminal via addition of ethers to quinone imine ketals (QIKs) has been developed under metal-free conditions. In the presence of tetrabutylammonium chloride and potassium persulfate (K2S2O8), QIKs couple efficiently with cyclic and acyclic ethers to give hemiaminals. This strategy offers an easy access to substituted hemiaminal ethers with high functional group tolerance in good to excellent yields.